Pengaruh Model Problem Based Learning Terhadap Hasil Belajar IPA Siswa Kelas V SD di SDIT Lentera Hati Ponorogo - Wafa Dani Hanifah (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2023)
Abstract: This study is intended to identify the influence of the use of the Problem Based Learning model on the science learning outcomes of grade V elementary school students. The approach used is quantitative with quasy experimental design methods. The results showed that the PBL model had a positive effect on student science learning outcomes. Proven based on the average science learning outcomes of experimental classes that were given treatment using the PBL model had a difference of 12.75 superior to control classes that did not use the PBL model in their learning activities. Through the results of the independent sample t-test hypothesis test, it was also found that the value of Sig. 0.001 < 0.05. It can be concluded that Ha is accepted so that there is a positive influence on the implementation of the Problem Based Learning model on the results of learning science for grade V students at SDIT Lentera Hati. Abstrak: Penelitian ini dimaksudkan guna mengidentifikasi pengaruh penggunaan model Problem Based Learning terhadap hasil belajar IPA siswa kelas V SD. Pendekatan yang digunakan ialah kuantitatif melalui metode eksperimen semu (quasy experimental design). Hasil penelitian menunjukkan bahwa model PBL berpengaruh positif terhadap hasil belajar IPA siswa. Ditunjukkan berdasarkan rata-rata hasil belajar IPA kelas eksperimen yang diberikan perlakuan memakai model PBL memiliki selisih 12,75 lebih unggul daripada kelas kontrol yang tidak memakai model PBL dalam kegiatan pembelajarannya. Melalui hasil uji hipotesis independent sample t-test juga didapati nilai Sig. 0,001 < 0,05. Dapat disimpulkan jika Ha diterima sehingga ada pengaruh positif pada pengimplementasian model Problem Based Learning akan hasil belajar IPA siswa kelas V di SDIT Lentera Hati.